Rapports à la conjugalité et à la sexualité chez les personnes âgées en Allemagne - Régis Schlagdenhauffen (Genre, Sexualité et Société)
The findings of surveys carried out in Germany on sexuality and partnership amongst elderly people show that, regardless of sexual orientation, changes in sexual activity are more a matter of marital status than age. 50% of coupled 60-year-old men and women claim to be enjoying a very active sex life. Also, the loss of a partner (death, separation) is the primary factor preventing elderly people from maintaining sexual activity (72% of single 60-year-olds say they have not had sexual relations in the last year). But whether single or in a relationship, these people consider sexuality to be something important that contributes to personal and relational well-being. However, in Germany as in France, men and women are not equal in the sexual marketplace, nor are they equal when it comes to being in a couple and even less so on the dating market... And things get even more complicated in the case of older gay men and lesbians. By comparing the findings of surveys carried out amongst heterosexuals and homosexuals one can see that with age aspirations considerably differ depending on whether one is male or female, gay or straight. Yet, one element seems to be shared by all: being in a relationship is seen as a plus as the other partner becomes the most important social resource (followed by children and grandchildren), regardless of sexual orientation.